2015
DOI: 10.4149/bll_2015_017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in dentistry students

Abstract: Abstract:The study evaluates dental caries prevalence in dentistry students. They represent a sample of individuals with good dental status, socio-economical level and access to dental care. The values of teeth number with decay and fi lling and values of surfaces of teeth with decay and fi lling indices in group with lower caries incidence give the information as to what could be achieved by systemic care and prevention of dental caries in whole population (Tab. 4. Ref. 25). Text in PDF www.elis.sk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…In the present study, students were divided into four groups, ages 19 to 25, 19 to 21, 21 to 23, and 23 to 25. Age and DMFT score had a strong statistically significant association (p 0.05).The findings of this study were consistent with another study had done on undergraduate dentistry students in Lahore with regard to age and gender.18 Other research using the same study design confirmed that female students had a greater caries frequency than male pupils 17,18 . The association between DMFT score and area was not significant in the current study (p=0.24), however the author of another study published in 2021 claimed that caries was complicated in urban areas, which was the contrary of the findings of the present study [18][19][20] .…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, students were divided into four groups, ages 19 to 25, 19 to 21, 21 to 23, and 23 to 25. Age and DMFT score had a strong statistically significant association (p 0.05).The findings of this study were consistent with another study had done on undergraduate dentistry students in Lahore with regard to age and gender.18 Other research using the same study design confirmed that female students had a greater caries frequency than male pupils 17,18 . The association between DMFT score and area was not significant in the current study (p=0.24), however the author of another study published in 2021 claimed that caries was complicated in urban areas, which was the contrary of the findings of the present study [18][19][20] .…”
Section: Discussionsupporting
confidence: 90%
“…We can conclude that Romani children do to use sufficiently the available dental care, but more often they seek urgent dental care in acute cases, when less invasive therapeutic procedures cannot be applied. Modern stomatology tends to use caries prevention and non-invasive therapeutic methods which can only be performed with a correctly timed early diagnostics of caries and regular dentist visits (Pavleova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…reflect the oral health condition of the whole population and what could be achieved by systemic care and prevention of dental caries in whole population. 10 The annual report of the Iraqi Ministry of Health in 2017 reported dental caries among the top 10causes of outpatient visits in Iraq, with a percentage of 2.1% of total visitors. 18 Most published studies about the prevalence of dental caries in Iraq were targeting school age children, [19][20][21] and this is similar to other developing countries, 22 and only few researches involved adult population, 19,[23][24][25][26][27] and only few studies investigated dental students.…”
Section: Originalmentioning
confidence: 99%
“…A major part of population in these countries has bad and neglected oral health caused by many different risk factors related to socio-economic and educational levels and difficult or no access to professional dental care. 10 While a small part of population, with higher socioeconomic state and good home care and better access for professional services since childhood, shows low caries index. 11 The main problem in dental caries is that its initial stages are asymptomatic; with symptoms appearing after the carious lesion has progressed into dentine.…”
Section: Introductionmentioning
confidence: 99%